A mentira tem perna curta? Elementos prosódicos como pistas para identificação de discurso enganoso - Silva, Remildo Barbosa da (2018)
There are few linguistic studies that attempt to investigate characteristics of lying speech. Most of them focus on physiological or psychological reactions. The focus of this work was to investigate the role of temporal prosodic elements; specifically, the speech rate and the pause in the characterization of the lying discourse as opposed to the true discourse. Information transmitted by speech is understood not only by the decoding of words, but also by the understanding of the attitudes of the speakers, in other words, the utterance is shaped by prosody, the primordial component of speech, which acts for a complete understanding of information. These elements can contribute significantly to the understanding of how speech is characterized in the two versions of utterances, making them useful in several areas, such as Forensic Phonetics and Communication. The data used in this study consists of audio recordings of native speakers of Brazilian Portuguese. They were analyzed using the Praat computer application. From the analysis of the data, we find specific temporal patterns for each of the two versions of utterances analyzed.